Tumor metabolism destruction via metformin-based glycolysis inhibition and glucose oxidase-mediated glucose deprivation for enhanced cancer therapy. (June 2022) - Meng, Xiangyu; Lu, Zhuoxuan; Lv, Qingyu; Jiang, Yongqiang; Zhang, Liming; Wang, Zhifei
Abstract: Cancer cells rely on glycolysis to support a high proliferation rate. Metformin (Met) is a promising drug for tumor treatment that targets hexokinase 2 (HK2) to block the glycolytic process, thereby further disrupting the metabolism of cancer cells. Herein, an intelligent nanomedicine based on glucose deprivation and glycolysis inhibition is creatively constructed for enhanced cancer synergistic treatment. In brief, Met and glucose oxidase (GOx) was encapsulated into histidine/zeolitic imidazolate framework-8 (His/ZIF-8), which was followed by coating with Arg-Gly-Asp (RGD) peptides to obtain the desired nanomedicine (Met/GOx@His/ZIF-8∼RGD). This smart nanomedicine presents the controllable Met and GOx release behavior in an acidic responsive manner. The liberated Met blocks the glycolysis process via suppressing the activity of HK2 and impairing ATP production, which activates the AMP-activated protein kinase (AMPK) pathway and p53 pathway and damages the Warburg effect, eventually leading to cells apoptosis. And the GOx boosts the glucose shortage for starvation therapy by depleting accumulated glucose. According to in vitro and in vivo assays, the combination of glycolysis inhibition and starvation therapy demonstrates efficient cancer cells growth suppression and superior antitumor properties compared to the Met based or GOx-mediated monotherapy. This work provides an advanced therapeutic strategy via disrupting cellular metabolism against cancer. Statement of significance: The obtained nanomedicine (Met/GOx@His/ZIF-8∼RGD) presents the controllable Met and glucose oxidase (GOx) release behavior in an acidic responsive manner. The liberated Met blocks the glycolysis process via suppressing the activity of HK2 and impairing ATP production, which activates the AMP-activated protein kinase (AMPK) pathway and p53 pathway and damages the Warburg effect, eventually leading to cells apoptosis. And the GOx boosts the glucose shortage for starvation therapy by depleting accumulated glucose. The combination of glycolysis inhibition and starvation therapy demonstrate the efficient suppression of cancer cells growth and the superior antitumor properties when compared to the Met based or GOx-mediated monotherapy. Graphical abstracts: Image, graphical abstract